Tire and Engine Sources Contribution to Vehicle Interior Noise and Vibration Exposure Levels - ABOUEL-SEOUD, Shawki (Archives of Acoustics, 2019)
The main objective of the research presented in this paper is to enhance driver-passengers comfort of a vehicle that in turn leads to better vehicle safety and stability. The focus was put on studying the interior vibration and noise contributions originated from tire-road and engine-transmission subsystems, due to their significant impact on the dynamic performance of the vehicle. The noise and vibration measurements were recorded at the driver’s head position and on the driver legs room. Furthermore, the influence of different tire types and road surface textures on the vehicle interior noise and vibration were considered. The results indicate that the widely used conventional engine mounts and tires in commercial vehicles cannot fulfill the conflicting requirements for the best isolation concerning both road surface and engine-transmission induced excitations. The values of driver’s head position sound pressure level and floor vibration acceleration broadband averages originate for engine-transmission are lower than that for tire-road interaction. Furthermore, the values of RMS, crest factor, kurtosis and IRI for the vehicle waveform were estimated for vehicle speeds, tire types and road surface textures. Moreover, the percentage contribution for both interior noise and vibration originated from tire-road interaction is higher than the one from vehicle engine-transmission system in all the vehicle speed range, tire type and road surface texture considered.